Authentication algorithm for participants of information interoperability in process of operating system remote loading on thin client - Gatchin, Yu.A.; Teploukhova, O.A. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2016)
Subject of Research.This paper presents solution of authentication problem for all components of information interoperabilityin process of operation system network loading on thin client from terminal server. System Definition. In the proposed solution operation system integrity check is made by hardware-software module, including USB-token with protected memory for secure storage of cryptographic keys and loader. The key requirement for the solution is mutual authentication of four participants: terminal server, thin client, token and user. We have created two algorithms for the problem solution. The first of the designed algorithms compares the encrypted one-time password (random number) with the reference value stored in the memory of the token and updates this number in case of successful authentication. The second algorithm uses the public and private keys of the token and the server. As a result of cryptographic transformation, participants are authenticated and the secure channel is formed between the token, thin client and terminal server. Main Results. Additional research was carried out to find out if the designed algorithms meet the necessary requirements. Criteria used included applicability in a multi-access terminal system architecture, potential threats evaluation and overall system security. According to analysis results, it is recommended to use the algorithm based on PKI due to its high scalability and usability. High level of data security is proved as a result of asymmetric cryptography application with the guarantee that participants' private keys are never sent in the authentication process. Practical Relevance. The designed PKI-based algorithm allows solving the problem with the use of cryptographic algorithms according to state standard even in its absence on asymmetric cryptography. Thus, it can be applied in the State Information Systems with increased requirements to information security.